Effect of 2-y n-3 long-chain polyunsaturated fatty acid supplementation on cognitive function in older people: a randomized, double-blind, controlled trial. - Dangour, A; Allen, E; Elbourne, D; Fasey, N; Fletcher, A; Hardy, P; Holder, G; Knight, R; Letley, L; Richards, M; Uauy, R (2010)
BACKGROUND: Increased consumption of n-3 (omega-3) long-chain polyunsaturated fatty acids (LC PUFAs), especially eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), may maintain cognitive function in later life. OBJECTIVE: We tested the hypothesis that n-3 LC PUFA supplementation would benefit cognitive function in cognitively healthy older people. DESIGN: At total of 867 cognitively healthy adults, aged 70-79 y, from 20 general practices in England and Wales were randomly assigned into a double-blind controlled trial of daily capsules providing 200 mg EPA plus 500 mg DHA or olive oil for 24 mo. Treatment-allocation codes were obtained from a central computerized randomization service. Trained research nurses administered a battery of cognitive tests, including the primary outcome, the California Verbal Learning Test (CVLT), at baseline and 24 mo. Intention-to-treat analysis of covariance, with adjustment for baseline cognitive scores, age, sex, and age at leaving full-time education, included 748 (86%) individuals who completed the study. RESULTS: The mean age of participants was 75 y; 55% of the participants were men. Withdrawals and deaths were similar in active (n = 49 and n = 9, respectively) and placebo (n = 53 and n = 8, respectively) arms. Mean (+/-SD) serum EPA and DHA concentrations were significantly higher in the active arm than in the placebo arm at 24 mo (49.9 +/- 2.7 mg EPA/L in the active arm compared with 39.1 +/- 3.1 mg EPA/L in the placebo arm; 95.6 +/- 3.1 mg DHA/L in the active arm compared with 70.7 +/- 2.9 mg DHA/L in the placebo arm). There was no change in cognitive function scores over 24 mo, and intention-to-treat analysis showed no significant differences between trial arms at 24 mo in the CVLT or any secondary cognitive outcome. CONCLUSIONS: Cognitive function did not decline in either study arm over 24 mo. The lack of decline in the control arm and the relatively short intervention period may have limited our ability to detect any potential beneficial effect of fish oil on cognitive function in this study. The Older People And n-3 Long-chain polyunsaturated fatty acids (OPAL) Study was registered at www.controlled-trials.com as ISRCTN 72331636.